2019
DOI: 10.1002/anie.201906645
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis at Surfaces with Atomic Precision: Taming Complexity and Perfection

Abstract: Scanning probe microscopy (SPM) is a powerful tool to study the structure and dynamics of molecules at surfaces and interfaces as well as to precisely manipulate atoms and molecules by applying an external force, by inelastic electron tunneling, or by means of an electric field. The rapid development of these SPM manipulation modes made it possible to achieve fine‐control over fundamental processes in the physics of interfaces as well as chemical reactivity, such as adsorption, diffusion, bond formation, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 145 publications
(224 reference statements)
0
13
0
Order By: Relevance
“…Moreover, it is reported that chemical reactions can occur in the molecule junctions. [7][8][9][10][11][12][13] Thus, single-molecule junction is an ideal platform to obtain the real-time information of chemical reactions. For example, Guo integrated a single molecule Pd catalyst into GMG-SMJ and achieved the real-time and full description of Suzuki-Miyaura cross-coupling reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is reported that chemical reactions can occur in the molecule junctions. [7][8][9][10][11][12][13] Thus, single-molecule junction is an ideal platform to obtain the real-time information of chemical reactions. For example, Guo integrated a single molecule Pd catalyst into GMG-SMJ and achieved the real-time and full description of Suzuki-Miyaura cross-coupling reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Milestones include on‐surface‐created polymers, [2] graphene nanoribbons, [3] a plethora of novel molecules and a wealth of one‐ and two‐dimensional nanostructures with intriguing properties [4, 5] . By contrast, the on‐surface covalent coupling by atom manipulation is still in its infancy, and only a few successful examples have been reported so far [6–9] …”
Section: Methodsmentioning
confidence: 99%
“…Solid-state materials, however, form a variety of complex, geometrical structures that are typically not balanced, hypercubic lattices [22,23,24,25]. Moreover, techniques such as scanning tunnelling microscopy and chemical synthesis mean that experimentalists now have an enormous degree of control over the lattice structure of the correlated materials they can synthesise [26,27,28,29,30,31,32,33]. Moire superlattices -stacked sheets of Van der Waals heterostructures -are such materials [34,35,36,37].…”
Section: Introductionmentioning
confidence: 99%